Bovine tuberculosis in cattle slaughtered at Addis Ababa abattoir in Ethiopia and workforce awareness of zoonotic risk - Fahmi Mohammed Ahmed; Musse Girma; Getnet Worku; Tekalign Tadesse; Girmay Medhin; Simon J. Waddell; Balako Gumi (PLoS ONE, 2025)
Background Bovine tuberculosis (bTB) is endemic and of zoonotic importance in Ethiopia. Despite this, there is limited recent information on the prevalence of bTB in cattle slaughtered at abattoirs. This study aimed to estimate the prevalence of bTB in cattle slaughtered at Addis Ababa municipality abattoir based on tuberculous lesions and region of difference (RD4) deletion typing and to assess the current practice and the awareness of occupational workers to zoonoses. Methods A total of 502 cattle slaughtered at the municipality abattoir (260 in the day shift and 242 in the night shift) were included in this cross-sectional study. Data collection and laboratory investigations included postmortem examination, culture and bacteriological examination, molecular characterization of positive isolates using region of difference (RD4) deletion typing and spoligotyping. Knowledge of zoonotic infection risk and practices was investigated through a questionnaire administered to 58 abattoir workers and 58 butchers. Results Based on postmortem examination, bTB suspected lesion was identified in 4.58% of cattle and it was significantly associated with, the age, breed and body condition of the animals. The detection of tuberculosis lesions during the night shift of the slaughter program was 1.54 times that of the day shift which is not statistically significant but warrants future study with a larger sample size. The gross lesions were predominately found in the lung and associated lymph nodes (65.5%). Of the 23 bTB suspected tuberculous lesions cultured, 11 (47.83%) tissue samples were culture-positive, and four isolates were RD4-positive, identifying M. bovis. Spoligotyping patterns were also effectively detected in four isolates. The observed spoligotype patterns were two SB1477 strains, and SB1176 and SB0133 strains. In the questionnaire survey, 79.31% of abattoir workers were aware of bTB, however, 93.10% of butchers did not know of bTB and understood less about preventing cross-infection. Conclusion Bovine tuberculosis is evident in cattle reaching the abattoir in Addis Ababa with nearly similar gross lesion pathology-based prevalence of bTB to prior findings reported from the same abattoir a decade ago. This suggests that despite efforts to control the disease in cattle, the prevalence remains largely unchanged. Although statistically non-significant, the trend showing higher odds of detecting tuberculous lesions during the night suggests a need for improved meat inspections during the night shift and the need for larger future studies.